Konflikt polityczny i natura ludzka: Machiavellego rozważania nad starożytną Republiką Rzymską i nowożytną Florencją oraz ich wpływ na współczesną świadomość demokratyczną - Marino, Mario (ETHICS IN PROGRESS, 2012)
The present paper stresses from a philological and anthropological point of view Machiavelli’s potential for thinking and practicing democracy in modern times. The first part disputes some Machiavellian myths, philologically demonstrating for example that Machiavelli never thought that ‘end justifies the means’. The second part brings to light the anthropological fundamentals of Machiavelli’s theory of political conflicts: special attention is paid to the doctrine of the opposite tendencies within the political bodies (the wish to command and the wish not to obey, the desire of oppressing and that of not to be oppressed) as well as to the theory of anthropological roots of ambition. The third and final part compares Machiavelli’s anthropological theory of political conflicts with both Marx’s economic interpretation of political conflicts and German philosophical anthropological explanation of human nature (Gehlen, Scheler, Plessner).